1987
DOI: 10.1007/bf00258203
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between liver cirrhosis and benign prostatic hyperplasia: A morphological study

Abstract: In elderly males hormonal changes occur, that are believed to cause benign prostatic hyperplasia (BPH). These are decreased testosterone production, an increased testosterone SHBG and a slightly increased estradiol production. Liver cirrhosis in males causes similar endocrine changes. We carried out a post mortem study evaluating the prostates of 51 men who died with liver cirrhosis compared with a similar group without any hepatic disease. The occurrence of BPH in cirrhotic subjects was diminished and delayed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Early work on risk factors for BPH suggested that men with alcoholic cirrhosis of the liver, which leads to decreased testosterone concentrations and in some cases increased estrogen concentrations (9), were less likely to have BPH nodules at autopsy, although study methods did not always take into account differing age distributions among cases and controls and findings were not entirely consistent between studies (40,41). Experimentally, both acute and repeated intake of higher levels of alcohol (e.g., 1.3 g/kg) results in transient plasma testosterone concentration depression (6-8) via decreased production and increased metabolism (8).…”
Section: Discussionmentioning
confidence: 98%
“…Early work on risk factors for BPH suggested that men with alcoholic cirrhosis of the liver, which leads to decreased testosterone concentrations and in some cases increased estrogen concentrations (9), were less likely to have BPH nodules at autopsy, although study methods did not always take into account differing age distributions among cases and controls and findings were not entirely consistent between studies (40,41). Experimentally, both acute and repeated intake of higher levels of alcohol (e.g., 1.3 g/kg) results in transient plasma testosterone concentration depression (6-8) via decreased production and increased metabolism (8).…”
Section: Discussionmentioning
confidence: 98%
“…21) In another study, healthy men were asked to consume a set amount of alcohol for four weeks along with balanced meals to examine the effect of alcohol on their testosterone level; the result showed that temporary alcohol consumption and repetitive alcohol consumption lowered the concentration of blood testosterone 22). Moreover, men with alcoholic liver cirrhosis tended to have hypogonadism or become feminized; in such cases, decreased testosterone levels and the resultant increase in estrogen levels lead to a lower risk of benign prostatic hyperplasia, based on autopsy results 2324). However, in other experiments androgens did not play a role as a growth factor of cultured prostate epithelial cells 25)…”
Section: Discussionmentioning
confidence: 99%
“…While some postmortem studies on the relationship between cirrhosis and BPH have demonstrated a weak prevalence [5][6][7][8], one has reported a high prevalence [9]. Although cirrhosis is known to cause some hormonal changes, their influence on BPH development is not clear.…”
Section: Introductionmentioning
confidence: 98%